Ultrasound assisted alkaline pre-treatment of sugarcane filter mud for performance enhancement in biogas production - Talha, Zahir; Hamid, Abdelbagi; Guo, Dong; Hassan, Muhammad; Mehryar, Esmaeil; Okinda, Cedric; Ding, Weimin (International Journal of Agricultural and Biological Engineering, 2018)
Sugar cane filter mud pre-treated by combined ultrasound-alkaline pre-treatment at different NaOH loading rates (0.25%-6%) and pre-treatment time (5 min to 60 min) performed in batch reactors under mesophilic conditions ((37±1)°C). Central composite design (CCD) was used to assess the effects on the chemical oxygen demand (COD) solubilisation, volatile fatty acid (VFA) concentration and methane yield. All pre-treatments were found significant to enhance methane yield (up to 39.49%) compared to the untreated filter mud. In general, results demonstrated the effectiveness of ultrasound assisted alkaline pre-treatment while increasing both NaOH loadings and pre-treatment time. Pre-treatment also increased the CODs solubilisation as well as VFA concentration, the optimal Initial CODs and VFA of 12 212 mg/L and 5830.97 mg/L, as determined by response surface methodology were noted on E9. Finally, modified Gompertz model was applied successfully to study kinetic of biogas production data, and showed an excellent fit. Keywords: anaerobic digestion, ultrasound-alkaline pre-treatment, biogas production, filter mud, enzymatic hydrolysis DOI: 10.25165/j.ijabe.20181101.3441 Citation: Talha Z, Hamid A, Guo D, Hassan M, Mehryar E, Okinda C, et al. Ultrasound assisted alkaline pre-treatment of sugarcane filter mud for performance enhancement in biogas production. Int J Agric & Biol Eng, 2018; 11(1): 226–231.